Mainz pouch urinary diversion with appendix stoma - Mori, Y (Hinyokika kiyo. Acta urologica Japonica, 1993)
The modified Mainz pouch urinary diversion was performed on 5 patients with bladder cancer using the submucosally embedded in situ appendix as a continence mechanism. It proved to be successful on 4 patients showing the complete urinary continence without difficulty in self catheterization. One patient became incontinent and a balloon catheter was retained. Advantages of the appendix stoma in the Mainz pouch are the reduction of the ileal segment to be isolated for creation of the pouch, relative simplicity of the operative technique, and the avoidance of use of foreign bodies such as metal staples or Marlex meshes